Characterization and reactivity of a terminal nickel(III)-oxygen adduct - MCDONALD, AIDAN (My University, 2015)
High-valent terminal metal-oxygen adducts are hypothesized to be the potent oxidizing reactants in late transition metal oxidation catalysis. In particular, examples of high-valent terminal nickel-oxygen adducts are scarce, meaning there is a dearth in the understanding of such oxidants. A monoanionic Ni(II)-bicarbonate complex has been found to react in a 1:1 ratio with the one-electron oxidant tris(4-bromophenyl)ammoniumyl hexachloroantimonate, yielding a thermally unstable intermediate in high yield (ca. 95%). Electronic absorption, electronic paramagnetic resonance, and X-ray absorption spectroscopies and density functional theory calculations confirm its description as a low-spin (S = 1/2), square planar Ni(III)-oxygen adduct. This rare example of a high-valent terminal nickel-oxygen complex performs oxidations of organic substrates, including 2,6-di-tert-butylphenol and triphenylphosphine, which are indicative of hydrogen atom abstraction and oxygen atom transfer reactivity, respectively.
PUBLISHED
Keywords: high-valent metals; metal-oxo species; nickel; oxidation catalysis; reactive intermediates